2005
DOI: 10.1002/dvdy.20463
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of Six3 and Six6 distribution in the developing and adult mouse brain

Abstract: Six3 and Six6 genes are two closely related members of the Six/sine oculis family of homeobox containing transcription factors. Their expression and function at early stages of embryonic development has been widely addressed in a variety of species. However, their mRNA distribution during late embryonic, postnatal, and adult brain barely has been analyzed. Here, we show that despite their initial overlap in the anterior neural plate, the expression of Six3 and Six6 progressively segregates to different regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 51 publications
3
43
0
Order By: Relevance
“…Six6 is strongly expressed in the retina and hypothalamus of all vertebrate species so far analysed (Aijaz et al, 2005;Conte and Bovolenta, 2007;Conte et al, 2005;Gallardo et al, 1999;Jean et al, 1999;Lopez-Rios et al, 1999). We previously used a two-step genome comparison strategy, followed by a highly reproducible transgenic analysis to dissect the regulatory code of Six3.2 (Conte and Bovolenta, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Six6 is strongly expressed in the retina and hypothalamus of all vertebrate species so far analysed (Aijaz et al, 2005;Conte and Bovolenta, 2007;Conte et al, 2005;Gallardo et al, 1999;Jean et al, 1999;Lopez-Rios et al, 1999). We previously used a two-step genome comparison strategy, followed by a highly reproducible transgenic analysis to dissect the regulatory code of Six3.2 (Conte and Bovolenta, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Later, Six3 is expressed in the anterior neuroectoderm, presumptive eye field, basal ganglia, prethalamus, hypothalamus and pituitary (Conte et al, 2005;Oliver et al, 1995). Early during development, Six3 maintains anterior forebrain identity and is required for neuroretinal specification (Geng et al, 2008;Lagutin et al, 2003;Lavado et al, 2008;Liu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The Sine oculis homeobox homolog (Six) gene family encodes a group of transcription factors that is related to homeobox-containing gene product in vertebrates by two conserved domains (Conte et al, 2005;Diaczok et al, 2008;Weasner and Kumar, 2009). Previous studies have reported that the Six family plays an important role in the entire development of the fly's visual system (Cheyette et al, 1994;Jean et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Earliest Six6 expression was detected in the floor of the diencephalic portion of the primitive forebrain, a region predicted to give rise to the neurohypophysis and to the hypothalamus. Later on, Six6 mRNA was found in the primordial tissues giving rise to mature pituitary: the Rathke's pouch and the infundibular recess (Conte et al, 2005). In the optic primordium, Six6 demarcates the presumptive ventral optic stalk and the ventral portion of the future neural retina (Jeans et al, 2006).…”
Section: Introductionmentioning
confidence: 99%